ANALYSIS OF STABILITY OF STEEL MEMBERS WITH ACCOUNT OF THE FIXING CONDITIONS AND SUPPORTS STIFFNESS - Kondel, V.; Loboda, D.; Кондель, В. М.; Лобода, Д. О.; Лобода, Д. А. (Харьковский национальный автомобильно-дорожный университет, 2017)
The authors have studied the stability of compressed steel structures and parts of machines with account of support conditions. The analysis of experimental and theoretical data of the behaviour of compressed structures and their members is provided. The new approaches to the critical-load design with account of supports stiffness are described.
АНАЛІЗ СТІЙКОСТІ СТАЛЕВИХ ЕЛЕМЕНТІВ З УРАХУВАННЯМ УМОВ ЇХ КРІПЛЕННЯ ТА ЖОРСТКОСТІ ОПОР
АНАЛИЗ УСТОЙЧИВОСТИ СТАЛЬНЫХ ЭЛЕМЕНТОВ С УЧЕТОМ УСЛОВИЙ ИХ КРЕПЛЕНИЯ И ЖЕСТКОСТИ ОПОР
Keywords: compressed steel members; buckling analysis; fixing conditions; supports stiffness; стиснуті сталеві елементи; розрахунки на стійкість; умови кріплення; жорсткість опор; сжатые стальные элементы; расчеты на устойчивость; условия крепления; жесткость опор; 621.88-21-026.564-034.14